2017
DOI: 10.5194/acp-17-14055-2017
|View full text |Cite
|
Sign up to set email alerts
|

Year-round record of bulk and size-segregated aerosol composition in central Antarctica (Concordia site) – Part 2: Biogenic sulfur (sulfate and methanesulfonate) aerosol

Abstract: Abstract. Multiple year-round (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) records of the bulk and size-segregated composition of aerosol were obtained at the inland site of Concordia located in East Antarctica. The well-marked maximum of non-seasalt sulfate (nssSO 4 ) in January (100 ± 28 ng m −3 versus 4.4 ± 2.3 ng m −3 in July) is consistent with observations made at the coast (280 ± 78 ng m −3 in January versus 16 ± 9 ng m −3 in July at Dumont d'Urville, for instance). In contrast, the well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 72 publications
17
56
2
Order By: Relevance
“…9e) falling on a straight line through zero). This then supports the assumption that in winter the size distributions of biogenic sulfate and MSA are the same and that the nssSO 4 / MSA ratio is constant over the entire size distribution (see also Legrand et al, 2017). The similarity of the nssSO 4 / MSA ratio over the entire size distribution was already pointed out by Jourdain et al (2007).…”
Section: Sulfate Relative To Sodium Fractionation In Wintersupporting
confidence: 75%
See 3 more Smart Citations
“…9e) falling on a straight line through zero). This then supports the assumption that in winter the size distributions of biogenic sulfate and MSA are the same and that the nssSO 4 / MSA ratio is constant over the entire size distribution (see also Legrand et al, 2017). The similarity of the nssSO 4 / MSA ratio over the entire size distribution was already pointed out by Jourdain et al (2007).…”
Section: Sulfate Relative To Sodium Fractionation In Wintersupporting
confidence: 75%
“…However, at Concordia the separation of the non-sea-salt and sea-salt sulfate modes is less straightforward than at coastal sites. Confirming several previous Antarctic studies, Legrand et al (2017) concluded that non-sea-salt sulfate present in winter there mainly originates from marine biogenic emissions. As seen in Fig.…”
Section: Sulfate Relative To Sodium Fractionation In Wintersupporting
confidence: 71%
See 2 more Smart Citations
“…This low winter and high summer seasonal difference has also been observed at coastal Antarctic sites, but the average concentrations were typically higher, with summertime concentrations ranging from 300 to 2000 cm −3 and wintertime concentrations from 10 to 200 cm −3 (Kim et al, 2017;Gras, 1993). Consistent with this seasonal difference in particle number concentrations, most summertime non-sea salt sulfate mass concentrations were at least 5 times higher than winter concentrations (Jourdain and Legrand, 2002;Weller and Wagenbach, 2007;Udisti et al, 2012;Legrand et al, 2017a;Asmi et al, 2018), likely because of the contributions from biogenic DMS emissions from the surrounding Southern Ocean. However, most sea salt aerosols had wintertime maximum concentrations with more than 2 times more Na + mass concentrations in winter than summer (Parungo et al, 1981;Wagenbach et al, 1998;Jourdain and Legrand, 2002;Weller and Wagenbach, 2007;Jourdain et al, 2008;Udisti et al, 2012;Legrand et al, 2017a, b;Asmi et al, 2018).…”
Section: Introductionsupporting
confidence: 64%